America's water: Agricultural water demands and the response of groundwater. Issue 14 (24th July 2016) - Ho, M.; Parthasarathy, V.; Etienne, E.; Russo, T. A.; Devineni, N.; Lall, U.
Abstract: Agricultural, industrial, and urban water use in the conterminous United States (CONUS) is highly dependent on groundwater that is largely drawn from nonsurficial wells (>30 m). We use a Demand‐Sensitive Drought Index to examine the impacts of agricultural water needs, driven by low precipitation, high agricultural water demand, or a combination of both, on the temporal variability of depth to groundwater across the CONUS. We characterize the relationship between changes in groundwater levels, agricultural water deficits relative to precipitation during the growing season, and winter precipitation. We find that declines in groundwater levels in the High Plains aquifer and around the Mississippi River Valley are driven by groundwater withdrawals used to supplement agricultural water demands. Reductions in agricultural water demands for crops do not, however, lead to immediate recovery of groundwater levels due to the demand for groundwater in other sectors in regions such as Utah, Maryland, and Texas. Key Points: Relationship between groundwater levels and a Demand‐Sensitive Drought Index is examined Depletion of groundwater continues even when agricultural demands are reduced Storage of winter precipitation critical to supplying agricultural water demands